Nonlinear Long‐Term Large Watershed Hydrologic Response to Wildfire and Climatic Dynamics Locally Increases Water Yields. Issue 7 (11th July 2018) - Wine, Michael L.; Makhnin, Oleg; Cadol, Daniel
Abstract: On all inhabited continents, wildfires are important ecological disturbances that influence water resources. As an exemplar of this global phenomenon, wildfire activity in the western United states increased in the 1980s and has continued to trend upward in subsequent decades. However, the hydrologic impact of wildfire has been difficult to ascertain at a continental scale due to the complexity of processes that influence critical zone dynamics. We calibrated Fuh's equation to wildfire‐impacted gauged watersheds and used the validated model to retrospectively quantify the proportion of streamflow attributed to wildfire hydrologic impacts from 1986 to 2015 across ungauged watersheds, accounting for interwatershed variability in water retention capacity and climate as well as how these factors interact with burned area and postwildfire vegetation recovery. Here we show that in parts of the western United States with high proportion of area burned by fire, wildfire‐linked streamflow accounts for as much as 20% of streamflow, rivaling or exceeding predicted climate change impacts. This analytic framework demonstrates that over a multidecadal period, the present trajectory of rising temperatures and increases in large wildfires may enhance the regional‐scale importance of wildfires in streamflow generation, thereby partially offsetting projected streamflow reductions due to rising temperatures and evaporative demand. Key Points: Globally, wildfires are important ecological disturbances that influence hydrologic processes, including regional water availability Hydrologic effects of wildfires in large ungauged basins are difficult to predict due to nonlinear hydrologic response to disturbance At continental scale, where optimal conditions for wildfire hydrologic impact converge, local water yields increase in large watersheds